Conductive interpenetrating network structure gel powder and preparation method and application thereof
By introducing conductive interpenetrating network structure gel powder into water-based polyurethane coatings, nylon, polyvinylpyrrolidone and PEDOT:PSS are used to form interpenetrating network structures, which solves the problems of low mechanical properties and insufficient corrosion resistance of water-based polyurethane coatings, and achieves higher mechanical properties and anti-static properties.
Patent Information
- Application Number
- CN202411785903.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-06
AI Technical Summary
Water-based polyurethane coatings have problems such as insufficient corrosion resistance, bubble formation and weak intermolecular forces in industrial applications, resulting in low mechanical properties, limiting their wide application.
Using a conductive interpenetrating network structure gel powder, a gel powder with an interpenetrating network structure was added by dissolving nylon powder and polyvinylpyrrolidone into an acidic solvent, and then a PEDOT:PSS aqueous solution was injected into the nanocellulose hydrogel solution under stirring conditions to form a gel powder with an interpenetrating network structure.
It improves the mechanical properties and corrosion resistance of gel materials, enhances the density and antistatic properties of polyurethane coatings, and solves the problems of low mechanical properties and insufficient corrosion resistance of water-based polyurethane coatings.
Smart Images

Figure CN119241905B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of honeycomb materials, and in particular relates to a conductive interpenetrating network structure gel powder and a preparation method and application thereof. Background Art
[0002] Polyurethane can be divided into two categories: solvent-based polyurethane and water-based polyurethane (WPU) due to its different dispersion medium. Water-based polyurethane is a polyurethane emulsion in which polyurethane resin uses water as the dispersion medium. In terms of structure, the rigid chain segment with ionic groups is hydrophilic, while the flexible chain segment plays a hydrophobic role; in terms of performance, it has the excellent characteristics of polyurethane resin. In terms of environmental impact, water-based polyurethane basically contains no or only trace amounts of organic compounds, and has the characteristics of being green, safe and non-toxic, low in manufacturing cost, and having many application fields. The demand for non-toxic, non-flammable and air-free resins has promoted the rapid development of water-based polyurethane.
[0003] The structure of waterborne polyurethane is a segmented polymer composed of soft segments and hard segments. Its performance is affected by its composition structure. The soft segments and hard segments form a unique separated microphase, which is the separated microphase that gives it many properties. Waterborne polyurethane has important application prospects in many industrial applications, such as coatings, adhesives, inks, glass fibers, paper pulp, synthetic leather, biomaterials, membranes and packaging films, and waterproof textiles.
[0004] The soft segment structure of waterborne polyurethane is composed of oligomer polyols, which have a great influence on its water resistance and mechanical strength. The hard segment structure is composed of isocyanate and small molecule chain extender, which has a great influence on the hardness, emulsion particle size and bonding performance of waterborne polyurethane after film formation. The structure of waterborne polyurethane can be adjusted in production. The soft segment provides flexibility and the hard segment provides rigidity. The main factors affecting its performance are the hydrogen bonds between hard-soft segments and hard-hard segments. With the increase of soft segment content, the degree of polymer crystallization and tensile properties are improved, but polyols are easily hydrolyzed, which will lead to poor water resistance. If you want to improve the hardness and bonding strength of waterborne polyurethane, you can increase the hard segment content appropriately, but if the hard segment content is too high, it will increase the chemical inertness of the chain segment, hinder the diffusion of the molecular chain, and lead to reduced bonding strength.
[0005] Waterborne polyurethane coatings not only require high gloss, color retention, scratch resistance and flame retardancy, but also protect materials from moisture, biological and chemical erosion. They are green, safe and pollution-free, and are often used in the fields of automobiles, construction, wood, paper, leather, and fabric coatings. However, waterborne polyurethane coatings use water as a carrier, and their lack of corrosion resistance is their biggest disadvantage, which to a certain extent affects their application in the industrial field. In addition, there are many problems in practical applications, such as a large number of bubbles generated during the reaction with water, which are difficult to eliminate and may remain in the coated film, affecting the various properties of the film. At the same time, due to their low solid content and weak intermolecular forces, the mechanical properties of waterborne polyurethane coatings are usually lower than those of traditional solvent-based polyurethane coatings, which has become a key bottleneck restricting their widespread application.
[0006] Blending modification is to physically blend the prepared WPU emulsion with other types of emulsions or some nanomaterials, and evenly disperse them through mechanical stirring or ultrasonic dispersion, so as to prepare the required functional coating. Nanomaterials refer to materials that have at least one dimension in the nanoscale range in three-dimensional space or are composed of them as basic units. Adding nanoparticles to polymers is one of the important methods to improve the performance of polymer materials. At present, there are many nanomaterials used to enhance and improve waterborne polyurethane, mainly including: nanocellulose, nanometal particles, nanocarbon materials, nanooxides, etc. CN118852963A discloses a heat-reflecting heat-insulating coating, in which nano-titanium dioxide is evenly dispersed in a cellulose aerogel matrix and a polyurethane coating, and the aggregation of nano-titanium dioxide is inhibited. The cellulose aerogel improves the flame retardant properties of the coating. CN117801653A discloses a highly elastic hydrophobic radiation-cured wood lacquer skin-feel coating, and the addition of hyperbranched nanocellulose hydrogel realizes the skin-tactile properties of the coating on the wood surface, and the physical and mechanical properties and durability of the coating are improved by reacting the -NH2 group in the hyperbranched nanocellulose hydrogel and the -NCO group in the radiation light-cured coating. CN110105531A and CN107474680A also disclose adding gel materials to the coating to improve the corresponding properties of the coating. However, the above-mentioned technology is only to add modified cellulose gel. As a natural fiber material, the mechanical properties of cellulose gel are relatively low; and cellulose gel has a large specific surface area. Due to the interaction between molecules and the influence of hydrogen bonds, cellulose gel is easily aggregated, so that its dispersibility and stability in polyurethane coatings are poor. At the same time, since the process of preparing cellulose gel is relatively complicated, the cost is high, and the yield is low, it is not suitable for large-scale industrialization.
[0007] On the other hand, waterborne polyurethane has properties such as wear resistance, oil resistance, corrosion resistance, compatibility and easy modification, and is widely used in medical equipment, aerospace and other fields. However, these resins are insulating and easily cause electrostatic discharge, which can damage electronic equipment in contact. This causes electrostatic discharge hazards, which can cause fires and explosions, severely limiting its application. At present, a variety of additives have been studied to reduce the surface resistivity of waterborne polyurethane materials, such as carbon black, surfactants, carbon nanotubes, conductive polymers, etc. Structurally, conductive polymers have good conductivity and good compatibility with polyurethane, making them ideal conductive fillers. Summary of the invention
[0008] The purpose of the present invention is to provide a conductive interpenetrating network structure gel powder and its preparation method and application. The gel powder prepared by the method not only has an interpenetrating network structure, but also the introduction of nylon resin further improves the mechanical properties of cellulose gel, and the nylon resin itself contains more amide groups, which greatly improves the compatibility of nanocellulose and polyurethane coating; and the addition of conductive components can manufacture composite polyurethane coating with long-term antistatic effect.
[0009] To achieve the above object, the present invention adopts the following technical solution:
[0010] A method for preparing a conductive interpenetrating network structure gel powder comprises the following steps:
[0011] (1) treating natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose;
[0012] (2) placing the deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution;
[0013] (3) dissolving nylon powder and polyvinyl pyrrolidone in an acidic solvent to obtain a nylon solution, and then adding the PEDOT:PSS aqueous solution to the nylon solution, stirring to obtain a nylon mixed solution; the mass ratio of polyvinyl pyrrolidone to nylon powder is (0.01-0.4):1;
[0014] (4) Under stirring conditions, injecting the nylon mixed solution into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection, exchanging with deionized water solvent to obtain a hydrogel with an interpenetrating network structure;
[0015] (5) The interpenetrating network structure hydrogel is freeze-dried and crushed to obtain a conductive interpenetrating network structure gel powder.
[0016] Cellulose is a common high molecular polymer in nature, widely found in plants such as cotton, hemp and wood, and has the advantages of good biocompatibility, renewability, biodegradability, environmental friendliness and non-toxicity. Nanocellulose is made from cellulose, and has at least one dimensional space size of less than 100nm. Nanocellulose composite hydrogel materials not only retain the unique physical and chemical properties of cellulose, such as hydrophilicity, biocompatibility, biodegradability, high chemical activity and dimensional stability, but also have new structural characteristics given by micro-nano processing technology, such as light weight, softness, high specific surface area, high crystallinity, high strength, high modulus and mild chemical activity. Because the surface of cellulose nanofibers has abundant hydroxyl groups, cellulose exhibits high hydrophilicity, and can quickly form a uniform and stable nanocellulose suspension in the coating, which is widely used.
[0017] However, nanocellulose has low mechanical properties and has limited performance improvement on the coating. In addition, nanocellulose is prone to agglomeration due to its large specific surface area and strong hydrogen bonding, and has problems such as poor compatibility with the matrix and uneven dispersion. In the previous work (CN118895018A), the inventor first prepared graphene hydrogel and then directly added nylon / nanocellulose mixed solution. The fibrous filler in this method can only be dispersed outside the hydrogel and cannot penetrate into the gel to form an interpenetrating structure. The nylon therein only plays a role of adhesion and has limited reinforcement. Subsequently, the inventor prepared a polyimide-nanocellulose conductive interpenetrating network structure gel powder. However, polyimide has poor processability and solubility. In order to configure the polyimide solution, it is necessary to start from the monomer raw material, first prepare a polyamic acid solution, and complete imidization in the process of preparing the gel. The above method not only prolongs the process steps; more importantly, polyamic acid, as an intermediate of polyimide, is extremely unstable and cannot be stored for a long time, which greatly limits its industrial application. Nylon itself not only has excellent mechanical properties, but is also soluble in some organic solvents but insoluble in water; in particular, the nylon solution itself is relatively stable and can be stored for a long time at room temperature.
[0018] Based on the above problems, the present invention first prepares nanocellulose gel and then prepares nylon nanofibers through a precipitation process. The precipitation method is a common process for preparing polymer nanofibers in the prior art, but directly pouring the nylon solution into the precipitate will produce micron or even millimeter-sized fibers, and it is impossible to prepare nanometer-sized fiber structures.
[0019] The present invention injects the nylon mixed solution into the nanocellulose hydrogel solution under stirring. Among them, the nanocellulose not only plays a role in forming an interpenetrating network structure; more importantly, under the state of rapid stirring, the nanocellulose fibers in the solution can play a "sickle"-like splitting role, so that the nylon mixed solution is split into bundles with smaller diameters, thereby reducing the diameter of the nylon fibers. In order to further make the fiber diameter reach the nanometer level, and also to enable the nylon solution to form a stable bundle structure in the rapidly stirred nanocellulose hydrogel solution and promote the generation of the nanofiber structure, the present invention adds a certain amount of polyvinyl pyrrolidone. On the one hand, the polyvinyl pyrrolidone molecule contains a pyridine ring structure, which can form a hydrogen bond with the amide group on the nylon, provide an adsorption force, and enable the nylon organic solution "bundle" to be stably dispersed in the nanocellulose hydrogel solution; on the other hand, polyvinyl pyrrolidone also has a hydrophilic effect, and can hydrate with water molecules in the nanocellulose hydrogel solution. When the nylon mixed solution is injected into the nanocellulose hydrogel solution, the adsorption force and hydration force of polyvinyl pyrrolidone cause polyvinyl pyrrolidone to disperse on the outer surface of the nylon organic solution "tow". Since polyvinyl pyrrolidone itself has a high viscosity, it can promote the stability of the "tow" structure. Under the shear force provided by stirring and the "cutting" effect of nanocellulose, the "tow" can gradually become longer and thinner, thereby increasing the aspect ratio of the nylon fiber and promoting the formation of the nanofiber structure. The molecular weight of polyvinyl pyrrolidone is not particularly limited, and its specific number average molecular weight can be 8000-200000.
[0020] Waterborne polyurethane is a waterborne polymer material with excellent performance. It has the advantages of being green, environmentally friendly, low manufacturing cost, and chemical resistance. However, it lacks antistatic properties, which leads to the need to add organic antistatic agents in industry. PEDOT:PSS is a conductive polymer with good water solubility and processability. PEDOT is a non-degenerate ground state conjugated polymer. After losing electrons, the main chain of PEDOT will have two structures: benzene type and quinone type. PSS, as a counterion, does not participate in the oxidation of PEDOT, but only stabilizes the structure of PEDOT. However, its sulfonic acid group can make PEDOT stably and evenly dispersed in water, giving PEDOT:PSS good hydrophilicity and excellent processability. The delocalized positive polaron on PEDOT and the negatively charged sulfonic acid group on PSS have a Coulomb effect, which makes PEDOT and PSS closely combined, so that the PEDOT:PSS aqueous dispersion has excellent environmental stability. At room temperature, its conductivity does not decrease significantly within a few years, and it can be used to prepare long-lasting antistatic products. However, as a conductive polymer, it usually needs to be added to the polyurethane coating in large quantities to effectively construct a connected conductive network, and the addition of a large amount of polymer is bound to reduce the mechanical properties and corrosion resistance of the polyurethane. In order to solve this problem, the present invention adds PEDOT:PSS during the preparation of the porous interpenetrating network. PEDOT:PSS is added to the nylon solution, and as the nylon precipitates, PEDOT:PSS gradually disperses to the fiber surface with nylon as the carrier, which is conducive to the construction of a conductive network of PEDOT:PSS in space; thus, only a small amount of PEDOT:PSS needs to be added to greatly improve the conductive properties of the gel material.
[0021] Nylon is soluble in acid, acetone and some alcohol organic solvents. The reason why the present invention selects acid as the solvent of nylon is that the acidic solvent can promote the formation of nanocellulose gel structure. In the process of injecting the nylon mixed solution, the violent stirring process will inevitably cause the destruction of the nanocellulose gel structure, and the acidic solution injected subsequently can repair the damaged gel structure and promote the stability of the gel structure. If organic solvents such as acetone are used, due to the addition of high-viscosity nylon, the damaged gel cannot be restored and cannot play a splitting role, affecting the formation of nylon nanofibers. On the other hand, as a conductive polymer, the PSS in PEDOT:PSS itself is insulating, but the hydrophilic PSS helps PEDOT to be more easily dispersed in the aqueous solution. After PEDOT:PSS is dispersed in the nylon solution, the processing effect of PSS has been exerted, and the presence of protons in the acidic solvent can cause changes in the conformation of PEDOT:PSS, so that the polymer chain combines with the protons in the acid, causing PSS to fall off from PEDOT:PSS, which can further improve the conductivity of the polymer.
[0022] The precipitation method is a common method for preparing fibers. During the forming process of the precipitated fibers, the polymer droplets enter the shear-flowing precipitating agent. Under the action of the shear force, the polymer droplets are stretched and elongated. At the same time, the organic solvent in the polymer droplets and the coagulant water in the precipitating agent undergo double diffusion, and the polymer fibers are gradually precipitated. The inventor also used the drop method to prepare polyimide precipitated nanofibers in previous work. However, the drop method is suitable for polymers with good fluidity (such as polyamic acid); for nylon polymers, the acidic solution has a large viscosity and poor fluidity. When the drop method is used to prepare nylon nanofibers, the drop size is difficult to control, and the droplets contact the nanocellulose gel aqueous solution at the liquid surface in a spherical structure, and the contact area between the droplets and the precipitated liquid is small; more importantly, the splitting effect of the nanocellulose at the liquid surface is difficult to play, and the precipitation of nylon will occur during the contact between the nylon solution and the precipitated liquid, and it is impossible to form an interpenetrating structure with the nanocellulose. In order to increase the contact area between the nylon solution and the precipitated liquid, the present invention uses an injection method to prepare the precipitated fibers. Under stirring conditions, a syringe with a nozzle is used to inject the nylon mixed solution into the nanocellulose hydrogel solution; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution. The nylon solution added by injection can make the solution contact with the precipitate in a fine filamentous structure. Compared with the droplets formed by the dripping method, the contact area with the precipitate is greatly increased, and the precipitated nylon fibers have better dispersion. Moreover, since the nozzle is inside the nanocellulose hydrogel solution, the splitting effect of the nanocellulose fibers is more fully exerted, so that the high-viscosity nylon mixed solution is split into filaments with smaller diameters, further reducing the diameter of the nylon fibers. Moreover, the injection process is more conducive to dispersing the conductive polymer into the gel powder, constructing a conductive network in three-dimensional space, and forming a conductive path inside the polyurethane coating after the polyurethane coating is infiltrated, thereby improving the antistatic performance of the polyurethane coating.
[0023] In general, under the splitting effect of nanocellulose and the auxiliary effect of polyvinyl pyrrolidone, the nylon mixed solution can form a fine liquid flow in the stirred nanocellulose hydrogel solution, and gradually precipitate to form nylon nanofibers, thereby forming an interpenetrating network structure with nanocellulose. As the nylon precipitates, PEDOT:PSS gradually disperses to the fiber surface with nylon as the carrier, which is conducive to the construction of a PEDOT:PSS conductive network in space; thus, only a small amount of PEDOT:PSS needs to be added to significantly improve the conductive properties of the gel material.
[0024] This composite functional gel material not only retains the original properties of the gel material, but also combines the high strength and thermal stability of nanocellulose and nylon fibers, as well as the high conductivity of PEDOT:PSS with the solution properties of hydrogels, making up for the "soft and weak" defects of nanocellulose gel materials in mechanical structure, and laying the foundation for potential application of gel development.
[0025] Furthermore, in step (1), the natural cellulose raw material is at least one of cotton, bamboo powder, waste paper, flax, sisal, straw, and bagasse; the treatment method includes at least one of high-pressure homogenization, acid hydrolysis, enzymatic hydrolysis, and TEMPO oxidation; the diameter of the nanocellulose is 10-100nm and the length is 5-20μm. Furthermore, the nanocellulose of the present invention is prepared by TEMPO oxidation. The full name of TEMPO is 2,2,6,6-tetramethylpiperidinyl oxide, which is an organic nitrogen oxide with weak oxidizing properties. This method has a short reaction time, is non-toxic, and has a low cost, and the morphology and size of the prepared nanocellulose are relatively uniform.
[0026] Furthermore, in step (2), the acidic steam bath is at least one of a formic acid steam bath, an acetic acid steam bath, a hydrochloric acid steam bath, and a nitric acid steam bath; and the steam bath treatment time is 2-10 hours. The steam bath method is to place the deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution.
[0027] Furthermore, in step (2), the nanocellulose content in the nanocellulose hydrogel solution is 0.5-2wt%; in step (3), the mass ratio of nanocellulose to nylon powder is (1-2):1; the nylon content in the nylon mixed solution is 1-5wt%; the acidic solvent is at least one of a formic acid solution and a sulfuric acid solution; the mass ratio of PEDOT:PSS in the nylon powder and the PEDOT:PSS aqueous solution is 1:(0.1-0.3). Both nylon and PEDOT:PSS are polar polymers, and the sulfonic acid group and the amide group in nylon can form a strong hydrogen bond force, which effectively improves the dispersibility of PEDOT:PSS on the basis of improving the attachment efficiency of PEDOT:PSS, and better constructs a conductive network.
[0028] Furthermore, in step (4), the nozzle has 1-4 nozzles; the nozzle aperture is 0.1-1mm; and the injection rate of the nylon mixed solution is 1-3mL / min. By injecting the nylon solution through the nozzles provided on the nozzle, the injection rate can be adjusted by the number of nozzles and the size of the nozzle aperture; compared with the dropwise addition method, the addition rate and morphology of the nylon solution are easier to control. There is no particular limitation on the number and aperture of the nozzles on the nozzle, and they can be adjusted according to the required injection rate. In particular, when multiple nozzles are used, the nozzles are evenly distributed on the nozzle, and the evenly distributed nozzles are more conducive to the uniform injection of the nylon solution into the nanocellulose gel solution, and the nanocellulose fibers can fully play a splitting role, so that the nylon mixed solution is split into smaller diameter bundles, thereby reducing the diameter of the nylon fibers. Furthermore, the number of nozzles is 1, and the nozzle aperture is 0.3mm. Furthermore, a 1mL or 2mL syringe commonly used on the market can be selected for injection. Furthermore, the injection rate is 1.2-2mL / min. By adjusting the injection rate, the nylon mixed solution can be fully dispersed into the nanocellulose hydrogel solution, and the splitting effect of nanocellulose can be fully exerted.
[0029] Furthermore, in step (3), the nylon is at least one of nylon 6, nylon 66, nylon 12, nylon 56, nylon 610, and nylon 1212; the mass fraction of the PEDOT:PSS aqueous solution is 1-5%; and the mass ratio of PEDOT to PSS in the PEDOT:PSS aqueous solution is 1:2-2.8.
[0030] Furthermore, in step (4), the stirring rate is 600-800 rpm. An appropriate stirring rate can prevent the nylon nanofiber aspect ratio from being reduced due to a too fast stirring rate, and can also prevent the defect of a thick diameter caused by a too slow stirring rate.
[0031] On the other hand, the present invention also provides an application of the conductive interpenetrating network structure gel powder, and the conductive interpenetrating network structure gel powder is used in the field of polyurethane coatings.
[0032] The polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion; and 0.5-5 parts of the gel powder of the interpenetrating network structure.
[0033] The conductive interpenetrating network structure gel powder prepared by injection method can make the nanocellulose and nylon nanofibers fully interact with each other, and the gel structure is more regular and the porosity is higher. The higher porosity is conducive to the full infiltration of polyurethane, and improves the bonding force between the gel powder and the polyurethane coating, thereby further improving the mechanical properties and anti-corrosion ability of the coating. In addition, the large number of hydroxyl groups on the surface of nanocellulose in the gel powder will hydrogen bond with PEDOT:PSS, nylon nanofibers and polyurethane matrix molecules, which enhances the interfacial interaction between the gel powder and the polyurethane matrix, gives full play to the conductive properties of the gel powder, and improves the antistatic ability of polyurethane. Nylon nanofibers have high mechanical properties, which solves the "soft and weak" defect of nanocellulose gel materials in mechanical structure. Nanocellulose and nylon nanofibers form an interpenetrating structure, which makes the two fully entangled, exerts a synergistic reinforcement effect, and improves the density and mechanical properties of the polyurethane coating.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] (1) The conductive interpenetrating network structure gel powder prepared by the injection method can make the nanocellulose and nylon nanofibers fully interact with each other, making the gel structure more regular and having a higher porosity. The higher porosity is conducive to the full infiltration of polyurethane, improving the bonding force between the gel powder and the polyurethane coating, thereby further improving the mechanical properties and anti-corrosion ability of the coating.
[0036] (2) First, prepare nanocellulose hydrogel and construct nanocellulose-based gel material. Then, inject the nylon mixed solution into the nanocellulose hydrogel solution under stirring. Under the splitting effect of nanocellulose and the auxiliary effect of polyvinyl pyrrolidone, the nylon mixed solution can form fine liquid flows in the stirred nanocellulose hydrogel solution and gradually precipitate to form nylon nanofibers, thereby forming an interpenetrating network structure with nanocellulose.
[0037] (3) PEDOT:PSS is added to the nylon solution. As the nylon precipitates, PEDOT:PSS gradually disperses onto the fiber surface using nylon as a carrier, which is beneficial for constructing a conductive network of PEDOT:PSS in space. Therefore, only a small amount of PEDOT:PSS needs to be added to significantly improve the conductive properties of the gel material.
[0038] (4) Compared with synthetic fibers such as polyimide, nylon fibers have low costs and nylon solutions do not need to be prepared in advance and can be used as needed, which greatly reduces production costs and process steps, and has broad market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 A simple injection device used in the present invention;
[0040] Figure 2 This is a scanning electron microscope image of the gel powder prepared in Example 10;
[0041] Figure 3 This is a scanning electron microscope image of the gel powder prepared in Comparative Example 1. DETAILED DESCRIPTION
[0042] The present invention is further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. In addition, it should be understood that after reading the content of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application. Unless otherwise specified, the preparation raw materials and process conditions in the following examples and comparative examples are consistent. Among them, the specific preparation process of nanocellulose in the following examples and comparative examples is as follows: (1) Removal of wax from bamboo powder: Add bamboo powder to a mixed solution composed of toluene and ethanol (volume ratio 3:1), mechanically stir for 24 hours, wash and dry, and set aside; (2) Removal of lignin from bamboo powder: Add the product of step (1) to a three-necked flask, then add 2wt% sodium chlorite solution, adjust the pH to 4, and react at 80°C for 6h, wash and dry, and set aside; (3) Removal of hemicellulose from bamboo powder: Add the product of step (2) to a 5wt% potassium hydroxide solution, stir at 90°C for 3h, wash and dry, and set aside; (4) Formation of nanocellulose: disperse bamboo cellulose powder in a mixed solution of TEMPO, sodium bromide and distilled water, slowly add sodium hypochlorite into the solution, stir evenly, adjust the pH to 10 and react for 4 hours, centrifuge and wash to obtain TEMPO-treated cellulose; the mass ratio of bamboo cellulose powder, TEMPO, sodium bromide and sodium hypochlorite is 1:0.02:0.1:2; place the TEMPO-treated cellulose in an ultrasonic cell crusher for 30 minutes, and freeze-dry to obtain nanocellulose with a diameter of 80 nm and a length of 10 μm.
[0043] Example 1
[0044] A method for preparing a conductive interpenetrating network structure gel powder comprises the following steps:
[0045] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose has a diameter of 80 nm and a length of 10 μm;
[0046] (2) placing a deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; the acidic steam bath is a formic acid steam bath; the steam bath treatment time is 4 hours; the nanocellulose content in the nanocellulose hydrogel solution is 0.5wt%;
[0047] (3) Dissolving nylon powder and polyvinyl pyrrolidone in an aqueous formic acid solution with a concentration of 88 wt% to obtain a nylon solution, wherein the number average molecular weight of the polyvinyl pyrrolidone is 30,000; then adding the PEDOT:PSS aqueous solution to the nylon solution, stirring to obtain a nylon mixed solution; the mass ratio of polyvinyl pyrrolidone to nylon powder is 0.1:1; the mass ratio of nanocellulose to nylon powder is 1:1; the nylon content in the nylon mixed solution is 1 wt%; the mass ratio of PEDOT:PSS in the nylon powder and the PEDOT:PSS aqueous solution is 1:0.1; the nylon is nylon 66; the mass fraction of the PEDOT:PSS aqueous solution is 3%; the mass ratio of PEDOT to PSS in the PEDOT:PSS aqueous solution is 1:2.6;
[0048] (4) Under stirring conditions, the nylon mixed solution is injected into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection, the solution is exchanged with deionized water solvent to obtain an interpenetrating network structure hydrogel; the injection is performed using a 1 mL medical syringe, i.e., the nozzle has a nozzle with a nozzle aperture of 0.3 mm; the nylon mixed solution injection rate is 1.2 mL / min; the stirring rate is 600 rpm;
[0049] (5) The interpenetrating network structure hydrogel is freeze-dried and crushed to obtain a conductive interpenetrating network structure gel powder.
[0050] A polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion and 4 parts of conductive interpenetrating network structure gel powder.
[0051] Example 2
[0052] A method for preparing a conductive interpenetrating network structure gel powder comprises the following steps:
[0053] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose has a diameter of 80 nm and a length of 10 μm;
[0054] (2) placing a deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; the acidic steam bath is a formic acid steam bath; the steam bath treatment time is 8 hours; the nanocellulose content in the nanocellulose hydrogel solution is 2wt%;
[0055] (3) Dissolving nylon powder and polyvinyl pyrrolidone in an aqueous formic acid solution with a concentration of 88 wt% to obtain a nylon solution, wherein the number average molecular weight of the polyvinyl pyrrolidone is 30,000; then adding the PEDOT:PSS aqueous solution to the nylon solution, stirring to obtain a nylon mixed solution; the mass ratio of polyvinyl pyrrolidone to nylon powder is 0.3:1; the mass ratio of nanocellulose to nylon powder is 2:1; the nylon content in the nylon mixed solution is 5 wt%; the mass ratio of PEDOT:PSS in the nylon powder and the PEDOT:PSS aqueous solution is 1:0.3; the nylon is nylon 66; the mass fraction of the PEDOT:PSS aqueous solution is 3%; the mass ratio of PEDOT to PSS in the PEDOT:PSS aqueous solution is 1:2.6;
[0056] (4) Under stirring conditions, the nylon mixed solution is injected into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection, the solution is exchanged with deionized water solvent to obtain an interpenetrating network structure hydrogel; the injection is performed using a 1 mL medical syringe, i.e., the nozzle has a nozzle with a nozzle aperture of 0.3 mm; the nylon mixed solution injection rate is 2 mL / min; the stirring rate is 800 rpm;
[0057] (5) The interpenetrating network structure hydrogel is freeze-dried and crushed to obtain a conductive interpenetrating network structure gel powder.
[0058] A polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion and 4 parts of conductive interpenetrating network structure gel powder.
[0059] Example 3
[0060] A method for preparing a conductive interpenetrating network structure gel powder comprises the following steps:
[0061] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose has a diameter of 80 nm and a length of 10 μm;
[0062] (2) placing a deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; the acidic steam bath is a formic acid steam bath; the steam bath treatment time is 8 hours; the nanocellulose content in the nanocellulose hydrogel solution is 0.5wt%;
[0063] (3) Dissolving nylon powder and polyvinyl pyrrolidone in an aqueous formic acid solution with a concentration of 88 wt% to obtain a nylon solution, wherein the number average molecular weight of the polyvinyl pyrrolidone is 30,000; then adding the PEDOT:PSS aqueous solution to the nylon solution, stirring to obtain a nylon mixed solution; the mass ratio of polyvinyl pyrrolidone to nylon powder is 0.3:1; the mass ratio of nanocellulose to nylon powder is 1:1; the nylon content in the nylon mixed solution is 5 wt%; the mass ratio of PEDOT:PSS in the nylon powder and the PEDOT:PSS aqueous solution is 1:0.1; the nylon is nylon 66; the mass fraction of the PEDOT:PSS aqueous solution is 3%; the mass ratio of PEDOT to PSS in the PEDOT:PSS aqueous solution is 1:2.6;
[0064] (4) Under stirring conditions, the nylon mixed solution is injected into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection, the solution is exchanged with deionized water solvent to obtain an interpenetrating network structure hydrogel; the injection is performed using a 1 mL medical syringe, i.e., the nozzle has a nozzle with a nozzle aperture of 0.3 mm; the injection rate of the nylon mixed solution is 2 mL / min; the stirring rate is 600 rpm;
[0065] (5) The interpenetrating network structure hydrogel is freeze-dried and crushed to obtain a conductive interpenetrating network structure gel powder.
[0066] A polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion and 4 parts of conductive interpenetrating network structure gel powder.
[0067] Example 4
[0068] A method for preparing a conductive interpenetrating network structure gel powder comprises the following steps:
[0069] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose has a diameter of 80 nm and a length of 10 μm;
[0070] (2) placing a deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; the acidic steam bath is a formic acid steam bath; the steam bath treatment time is 5 hours; the nanocellulose content in the nanocellulose hydrogel solution is 1wt%;
[0071] (3) Dissolving nylon powder and polyvinyl pyrrolidone in an aqueous formic acid solution with a concentration of 88 wt% to obtain a nylon solution, wherein the number average molecular weight of the polyvinyl pyrrolidone is 30,000; then adding the PEDOT:PSS aqueous solution to the nylon solution, stirring to obtain a nylon mixed solution; the mass ratio of polyvinyl pyrrolidone to nylon powder is 0.15:1; the mass ratio of nanocellulose to nylon powder is 1.2:1; the nylon content in the nylon mixed solution is 2 wt%; the mass ratio of PEDOT:PSS in the nylon powder and the PEDOT:PSS aqueous solution is 1:0.15; the nylon is nylon 66; the mass fraction of the PEDOT:PSS aqueous solution is 3%; the mass ratio of PEDOT to PSS in the PEDOT:PSS aqueous solution is 1:2.6;
[0072] (4) Under stirring conditions, the nylon mixed solution is injected into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection, the solution is exchanged with deionized water solvent to obtain an interpenetrating network structure hydrogel; the injection is performed using a 1 mL medical syringe, i.e., the nozzle has a nozzle with a nozzle aperture of 0.3 mm; the nylon mixed solution injection rate is 1.4 mL / min; the stirring rate is 650 rpm;
[0073] (5) The interpenetrating network structure hydrogel is freeze-dried and crushed to obtain a conductive interpenetrating network structure gel powder.
[0074] A polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion and 4 parts of conductive interpenetrating network structure gel powder.
[0075] Example 5
[0076] A method for preparing a conductive interpenetrating network structure gel powder comprises the following steps:
[0077] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose has a diameter of 80 nm and a length of 10 μm;
[0078] (2) placing a deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; the acidic steam bath is a formic acid steam bath; the steam bath treatment time is 7 hours; the nanocellulose content in the nanocellulose hydrogel solution is 1.6wt%;
[0079] (3) Dissolving nylon powder and polyvinyl pyrrolidone in an aqueous formic acid solution with a concentration of 88 wt% to obtain a nylon solution, wherein the number average molecular weight of the polyvinyl pyrrolidone is 30,000; then adding the PEDOT:PSS aqueous solution to the nylon solution, stirring to obtain a nylon mixed solution; the mass ratio of polyvinyl pyrrolidone to nylon powder is 0.25:1; the mass ratio of nanocellulose to nylon powder is 1.8:1; the nylon content in the nylon mixed solution is 4 wt%; the mass ratio of PEDOT:PSS in the nylon powder and the PEDOT:PSS aqueous solution is 1:0.25; the nylon is nylon 66; the mass fraction of the PEDOT:PSS aqueous solution is 3%; the mass ratio of PEDOT to PSS in the PEDOT:PSS aqueous solution is 1:2.6;
[0080] (4) Under stirring conditions, the nylon mixed solution is injected into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection, the solution is exchanged with deionized water solvent to obtain an interpenetrating network structure hydrogel; the injection is performed using a 1 mL medical syringe, i.e., the nozzle has a nozzle with a nozzle aperture of 0.3 mm; the nylon mixed solution injection rate is 1.8 mL / min; the stirring rate is 750 rpm;
[0081] (5) The interpenetrating network structure hydrogel is freeze-dried and crushed to obtain a conductive interpenetrating network structure gel powder.
[0082] A polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion and 4 parts of conductive interpenetrating network structure gel powder.
[0083] Example 6
[0084] A method for preparing a conductive interpenetrating network structure gel powder comprises the following steps:
[0085] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose has a diameter of 80 nm and a length of 10 μm;
[0086] (2) placing a deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; the acidic steam bath is a formic acid steam bath; the steam bath treatment time is 6 hours; the nanocellulose content in the nanocellulose hydrogel solution is 1.5wt%;
[0087] (3) Dissolving nylon powder and polyvinyl pyrrolidone in an aqueous formic acid solution with a concentration of 88 wt% to obtain a nylon solution, wherein the number average molecular weight of the polyvinyl pyrrolidone is 30,000; then adding the PEDOT:PSS aqueous solution to the nylon solution, stirring to obtain a nylon mixed solution; the mass ratio of polyvinyl pyrrolidone to nylon powder is 0.04:1; the mass ratio of nanocellulose to nylon powder is 1.5:1; the nylon content in the nylon mixed solution is 3 wt%; the mass ratio of PEDOT:PSS in the nylon powder and the PEDOT:PSS aqueous solution is 1:0.2; the nylon is nylon 66; the mass fraction of the PEDOT:PSS aqueous solution is 3%; the mass ratio of PEDOT to PSS in the PEDOT:PSS aqueous solution is 1:2.6;
[0088] (4) Under stirring conditions, the nylon mixed solution is injected into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection, the solution is exchanged with deionized water solvent to obtain an interpenetrating network structure hydrogel; the injection is performed using a 1 mL medical syringe, i.e., the nozzle has a nozzle with a nozzle aperture of 0.3 mm; the nylon mixed solution injection rate is 1.5 mL / min; the stirring rate is 700 rpm;
[0089] (5) The interpenetrating network structure hydrogel is freeze-dried and crushed to obtain a conductive interpenetrating network structure gel powder.
[0090] A polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion and 4 parts of conductive interpenetrating network structure gel powder.
[0091] Example 7
[0092] A method for preparing a conductive interpenetrating network structure gel powder comprises the following steps:
[0093] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose has a diameter of 80 nm and a length of 10 μm;
[0094] (2) placing a deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; the acidic steam bath is a formic acid steam bath; the steam bath treatment time is 6 hours; the nanocellulose content in the nanocellulose hydrogel solution is 1.5wt%;
[0095] (3) Dissolving nylon powder and polyvinyl pyrrolidone in an aqueous formic acid solution with a concentration of 88 wt% to obtain a nylon solution, wherein the number average molecular weight of the polyvinyl pyrrolidone is 30,000; then adding the PEDOT:PSS aqueous solution to the nylon solution, stirring to obtain a nylon mixed solution; the mass ratio of polyvinyl pyrrolidone to nylon powder is 0.4:1; the mass ratio of nanocellulose to nylon powder is 1.5:1; the nylon content in the nylon mixed solution is 3 wt%; the mass ratio of PEDOT:PSS in the nylon powder and the PEDOT:PSS aqueous solution is 1:0.2; the nylon is nylon 66; the mass fraction of the PEDOT:PSS aqueous solution is 3%; the mass ratio of PEDOT to PSS in the PEDOT:PSS aqueous solution is 1:2.6;
[0096] (4) Under stirring conditions, the nylon mixed solution is injected into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection, the solution is exchanged with deionized water solvent to obtain an interpenetrating network structure hydrogel; the injection is performed using a 1 mL medical syringe, i.e., the nozzle has a nozzle with a nozzle aperture of 0.3 mm; the nylon mixed solution injection rate is 1.5 mL / min; the stirring rate is 700 rpm;
[0097] (5) The interpenetrating network structure hydrogel is freeze-dried and crushed to obtain a conductive interpenetrating network structure gel powder.
[0098] A polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion and 4 parts of conductive interpenetrating network structure gel powder.
[0099] Example 8
[0100] A method for preparing a conductive interpenetrating network structure gel powder comprises the following steps:
[0101] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose has a diameter of 80 nm and a length of 10 μm;
[0102] (2) placing a deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; the acidic steam bath is a formic acid steam bath; the steam bath treatment time is 6 hours; the nanocellulose content in the nanocellulose hydrogel solution is 1.5wt%;
[0103] (3) Dissolving nylon powder and polyvinyl pyrrolidone in an aqueous formic acid solution with a concentration of 88 wt% to obtain a nylon solution, wherein the number average molecular weight of the polyvinyl pyrrolidone is 30,000; then adding the PEDOT:PSS aqueous solution to the nylon solution, stirring to obtain a nylon mixed solution; the mass ratio of polyvinyl pyrrolidone to nylon powder is 0.2:1; the mass ratio of nanocellulose to nylon powder is 1.5:1; the nylon content in the nylon mixed solution is 3 wt%; the mass ratio of PEDOT:PSS in the nylon powder and the PEDOT:PSS aqueous solution is 1:0.2; the nylon is nylon 66; the mass fraction of the PEDOT:PSS aqueous solution is 3%; the mass ratio of PEDOT to PSS in the PEDOT:PSS aqueous solution is 1:2.6;
[0104] (4) Under stirring conditions, the nylon mixed solution is injected into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection, the solution is exchanged with deionized water solvent to obtain an interpenetrating network structure hydrogel; the injection is performed using a 1 mL medical syringe, i.e., the nozzle has a nozzle with a nozzle aperture of 0.3 mm; the nylon mixed solution injection rate is 1 mL / min; the stirring rate is 700 rpm;
[0105] (5) The interpenetrating network structure hydrogel is freeze-dried and crushed to obtain a conductive interpenetrating network structure gel powder.
[0106] A polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion and 4 parts of conductive interpenetrating network structure gel powder.
[0107] Example 9
[0108] A method for preparing a conductive interpenetrating network structure gel powder comprises the following steps:
[0109] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose has a diameter of 80 nm and a length of 10 μm;
[0110] (2) placing a deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; the acidic steam bath is a formic acid steam bath; the steam bath treatment time is 6 hours; the nanocellulose content in the nanocellulose hydrogel solution is 1.5wt%;
[0111] (3) Dissolving nylon powder and polyvinyl pyrrolidone in an aqueous formic acid solution with a concentration of 88 wt% to obtain a nylon solution, wherein the number average molecular weight of the polyvinyl pyrrolidone is 30,000; then adding the PEDOT:PSS aqueous solution to the nylon solution, stirring to obtain a nylon mixed solution; the mass ratio of polyvinyl pyrrolidone to nylon powder is 0.2:1; the mass ratio of nanocellulose to nylon powder is 1.5:1; the nylon content in the nylon mixed solution is 3 wt%; the mass ratio of PEDOT:PSS in the nylon powder and the PEDOT:PSS aqueous solution is 1:0.2; the nylon is nylon 66; the mass fraction of the PEDOT:PSS aqueous solution is 3%; the mass ratio of PEDOT to PSS in the PEDOT:PSS aqueous solution is 1:2.6;
[0112] (4) Under stirring conditions, the nylon mixed solution is injected into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection, the hydrogel with an interpenetrating network structure is obtained by exchanging with deionized water solvent; the injection is performed using a 1 mL medical syringe, that is, the nozzle has a nozzle with a nozzle aperture of 0.3 mm; the nylon mixed solution injection rate is 3 mL / min; the stirring rate is 700 rpm;
[0113] (5) The interpenetrating network structure hydrogel is freeze-dried and crushed to obtain a conductive interpenetrating network structure gel powder.
[0114] A polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion and 4 parts of conductive interpenetrating network structure gel powder.
[0115] Example 10
[0116] A method for preparing a conductive interpenetrating network structure gel powder comprises the following steps:
[0117] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose has a diameter of 80 nm and a length of 10 μm;
[0118] (2) placing a deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; the acidic steam bath is a formic acid steam bath; the steam bath treatment time is 6 hours; the nanocellulose content in the nanocellulose hydrogel solution is 1.5wt%;
[0119] (3) Dissolving nylon powder and polyvinyl pyrrolidone in an aqueous formic acid solution with a concentration of 88 wt% to obtain a nylon solution, wherein the number average molecular weight of the polyvinyl pyrrolidone is 30,000; then adding the PEDOT:PSS aqueous solution to the nylon solution, stirring to obtain a nylon mixed solution; the mass ratio of polyvinyl pyrrolidone to nylon powder is 0.2:1; the mass ratio of nanocellulose to nylon powder is 1.5:1; the nylon content in the nylon mixed solution is 3 wt%; the mass ratio of PEDOT:PSS in the nylon powder and the PEDOT:PSS aqueous solution is 1:0.2; the nylon is nylon 66; the mass fraction of the PEDOT:PSS aqueous solution is 3%; the mass ratio of PEDOT to PSS in the PEDOT:PSS aqueous solution is 1:2.6;
[0120] (4) Under stirring conditions, the nylon mixed solution is injected into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection, the solution is exchanged with deionized water solvent to obtain an interpenetrating network structure hydrogel; the injection is performed using a 1 mL medical syringe, i.e., the nozzle has a nozzle with a nozzle aperture of 0.3 mm; the nylon mixed solution injection rate is 1.5 mL / min; the stirring rate is 700 rpm;
[0121] (5) The interpenetrating network structure hydrogel is freeze-dried and crushed to obtain a conductive interpenetrating network structure gel powder.
[0122] A polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion and 4 parts of conductive interpenetrating network structure gel powder.
[0123] Comparative Example 1
[0124] A method for preparing a conductive interpenetrating network structure gel powder comprises the following steps:
[0125] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose has a diameter of 80 nm and a length of 10 μm;
[0126] (2) placing a deionized water dispersion of nanocellulose and polyvinyl pyrrolidone in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; the acidic steam bath is a formic acid steam bath; the steam bath treatment time is 6 hours; the nanocellulose content in the nanocellulose hydrogel solution is 1.5wt%;
[0127] (3) Dissolving nylon powder in 88wt% formic acid aqueous solution to obtain a nylon solution, wherein the number average molecular weight of polyvinyl pyrrolidone is 30000; then adding PEDOT:PSS aqueous solution to the nylon solution, stirring to obtain a nylon mixed solution; the mass ratio of polyvinyl pyrrolidone to nylon powder is 0.2:1; the mass ratio of nanocellulose to nylon powder is 1.5:1; the nylon content in the nylon mixed solution is 3wt%; the mass ratio of PEDOT:PSS in the nylon powder and PEDOT:PSS aqueous solution is 1:0.2; the nylon is nylon 66; the mass fraction of PEDOT:PSS aqueous solution is 3%; the mass ratio of PEDOT to PSS in the PEDOT:PSS aqueous solution is 1:2.6;
[0128] (4) Under stirring conditions, the nylon mixed solution is injected into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection, the solution is exchanged with deionized water solvent to obtain an interpenetrating network structure hydrogel; the injection is performed using a 1 mL medical syringe, i.e., the nozzle has a nozzle with a nozzle aperture of 0.3 mm; the nylon mixed solution injection rate is 1.5 mL / min; the stirring rate is 700 rpm;
[0129] (5) The interpenetrating network structure hydrogel is freeze-dried and crushed to obtain a conductive interpenetrating network structure gel powder.
[0130] A polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion and 4 parts of conductive interpenetrating network structure gel powder.
[0131] Comparative Example 2
[0132] A method for preparing a conductive interpenetrating network structure gel powder comprises the following steps:
[0133] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose has a diameter of 80 nm and a length of 10 μm;
[0134] (2) placing a deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; the acidic steam bath is a formic acid steam bath; the steam bath treatment time is 6 hours; the nanocellulose content in the nanocellulose hydrogel solution is 1.5wt%;
[0135] (3) Dissolving nylon powder and polyvinyl pyrrolidone in an aqueous formic acid solution with a concentration of 88 wt% to obtain a nylon solution, wherein the number average molecular weight of the polyvinyl pyrrolidone is 30,000; then adding the PEDOT:PSS aqueous solution to the nylon solution, stirring to obtain a nylon mixed solution; the mass ratio of polyvinyl pyrrolidone to nylon powder is 0.2:1; the mass ratio of nanocellulose to nylon powder is 1.5:1; the nylon content in the nylon mixed solution is 3 wt%; the mass ratio of PEDOT:PSS in the nylon powder and the PEDOT:PSS aqueous solution is 1:0.2; the nylon is nylon 66; the mass fraction of the PEDOT:PSS aqueous solution is 3%; the mass ratio of PEDOT to PSS in the PEDOT:PSS aqueous solution is 1:2.6;
[0136] (4) Under stirring conditions, the nylon mixed solution was added dropwise to the nanocellulose hydrogel solution; after the addition was completed, the solution was exchanged with deionized water solvent to obtain an interpenetrating network structure hydrogel; the nylon mixed solution dropwise acceleration rate was 1.5 mL / min; the stirring rate was 700 rpm;
[0137] (5) The interpenetrating network structure hydrogel is freeze-dried and crushed to obtain a conductive interpenetrating network structure gel powder.
[0138] A polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion and 4 parts of conductive interpenetrating network structure gel powder.
[0139] Performance test: The polyurethane coatings prepared in Examples 1-10 and Comparative Examples 1-2 were subjected to hardness test (GB / T6739-2006), paint film adhesion test (GB / T 5210-2006), salt spray resistance test (GB / T1771-2007) and surface resistance test (ASTM D257); the test results are shown in Table 1.
[0140]
[0141] Figure 2-3 The following are the scanning electron microscope images of the gel powder prepared in Example 10 and Comparative Example 1. Figure 2It can be seen that the gel prepared by the solution internal injection method has a larger pore size, which greatly improves the porosity of the gel, is beneficial to the full infiltration of the polyurethane material, improves the interface performance between the gel powder and the polyurethane resin, and further improves the mechanical strength and corrosion resistance of the coating. There is no agglomeration phenomenon in the figure, indicating that the nylon and PEDOT:PSS mixed solution prepared by the injection method is evenly dispersed, preventing the occurrence of agglomeration. Comparative Example 1 shows that polyvinyl pyrrolidone needs to be added to the nylon solution in advance. If it is added to the nanocellulose aqueous dispersion in advance, due to the abundant hydroxyl groups on the surface of the nanocellulose, it will form strong hydrogen bonds with polyvinyl pyrrolidone and cannot adhere to the surface of the subsequently added nylon, so that the nylon solution "bundles" cannot be stably dispersed in the nanocellulose hydrogel solution, affecting the formation of polymer nanofibers. From Figure 3 It can also be seen that the prepared gel powder has no fiber structure, PEDOT:PSS cannot form a conductive network, and the antistatic performance is reduced. Comparative Example 2 uses the drop method to prepare the gel powder. Due to the high viscosity and poor fluidity of the nylon polymer solution, when the drop method is used to prepare nylon nanofibers, the drop size is difficult to control, and the droplet contacts the nanocellulose gel aqueous solution at the liquid surface in a spherical structure, and the contact area between the droplet and the precipitate is small; the splitting effect of the nanocellulose at the liquid surface is difficult to play, and the nylon will precipitate during the contact between the nylon solution and the precipitate, and it is impossible to form an interpenetrating structure with the nanocellulose.
[0142] The above description is only a preferred embodiment of the present invention and does not constitute any other form of limitation to the present invention. Any modification or equivalent change made based on the technical essence of the present invention still falls within the scope of protection required by the present invention.
Claims
1. A method for preparing a conductive interpenetrating network structure gel powder, characterized in that: The following steps are involved: (1) treating natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; (2) placing the deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; (3) dissolving nylon powder and polyvinyl pyrrolidone in an acidic solvent to obtain a nylon solution, then adding the PEDOT:PSS aqueous solution to the nylon solution, and stirring to obtain a nylon mixed solution; The mass ratio of polyvinyl pyrrolidone to nylon powder is (0.01-0.4):1; (4) Under stirring conditions, injecting the nylon mixed solution into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection, exchanging with deionized water solvent to obtain a hydrogel with an interpenetrating network structure; (5) The interpenetrating network structure hydrogel is freeze-dried and crushed to obtain a conductive interpenetrating network structure gel powder.
2. The method for preparing a conductive interpenetrating network structure gel powder according to claim 1, characterized in that: In step (1), the diameter of the nanocellulose is 10-100 nm and the length is 5-20 μm.
3. The method for preparing a conductive interpenetrating network structure gel powder according to claim 1, characterized in that: In step (2), the acidic steam bath is at least one of a formic acid steam bath, an acetic acid steam bath, a hydrochloric acid steam bath, and a nitric acid steam bath; and the steam bath treatment time is 2-10 hours.
4. The method for preparing a conductive interpenetrating network structure gel powder according to claim 1, characterized in that: The nanocellulose content in the nanocellulose hydrogel solution of step (2) is 0.5-2wt%; the mass ratio of nanocellulose to nylon powder in step (3) is (1-2):1; the nylon content in the nylon mixed solution is 1-5wt%; the acidic solvent is at least one of formic acid solution and sulfuric acid solution; the mass ratio of PEDOT:PSS in the nylon powder and PEDOT:PSS aqueous solution is 1:(0.1-0.3).
5. The method for preparing a conductive interpenetrating network structure gel powder according to claim 1, characterized in that: In step (4), the nozzle has 1-4 nozzles; the nozzle aperture is 0.1-1 mm; and the nylon mixed solution injection rate is 1-3 mL / min.
6. The method for preparing a conductive interpenetrating network structure gel powder according to claim 1, characterized in that: In step (3), the nylon is at least one of nylon 6, nylon 66, nylon 12, nylon 56, nylon 610, and nylon 1212; the mass fraction of the PEDOT:PSS aqueous solution is 1-5%; and the mass ratio of PEDOT to PSS in the PEDOT:PSS aqueous solution is 1:2-2.
8.
7. The method for preparing a conductive interpenetrating network structure gel powder according to claim 1, characterized in that: The stirring rate in step (4) is 600-800 rpm.
8. A conductive interpenetrating network structure gel powder, characterized in that: The conductive interpenetrating network structure gel powder is prepared by the preparation method of any one of claims 1 to 7.
9. An application of a conductive interpenetrating network structure gel powder as claimed in claim 8, characterized in that: Conductive interpenetrating network structure gel powder is used in the field of polyurethane coatings.
10. A polyurethane coating, characterized in that: The invention comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion; and 0.5-5 parts of the conductive interpenetrating network structure gel powder according to claim 8.
Citation Information
Patent Citations
Environment-friendly antibacterial waterborne wood coating
CN107474680A
Preparation method of antibacterial coating used for paper
CN110105531A
Preparation method of high-elastic hydrophobic radiation curing wood paint skin feeling coating
CN117801653A
Heat reflection heat insulation coating and preparation method thereof
CN118852963A
Gel powder with high mechanical property as well as preparation method and application of gel powder
CN118895018A